Sensors Special Issue: "Vibration Energy Harvesting for Wireless Sensors" - Hadas, Zdenek; Zelenika, Saša; Pakrashi, Vikram (Sensors (Basel, Switzerland), 2022)
Mechanical vibrations occur in the operation of most technical systems [...].
Keywords: vibrace; Electric Power Supplies; Vibration; zdroje elektrické energie; techniky fyzikální terapie; Physical Therapy Modalities